Training as experience and collective production of knowledge in the National Pedagogical Expedition - Unda Bernal, María del Pilar
These words of Pepe Mujica (2013) in conversation with a European journalist, who expresses his surprise at his way of acting as ruler and his admiration for his ideas, become a good preamble to highlight the commitment of the Pedagogical Expedition to build the collective and break the insularity and isolation to which many teachers have been subjected in educational institutions. This is what we are working on in this article, highlighting the importance of the Pedagogical Expedition in the construction of collective perspectives on education.